Electronic performance and career development supporting system for multiple evaluators "Sistem Prestasi dan Peningkatan Kerjaya" / Noreen Muslim - Muslim, Noreen (2006)
This project focuses on performance evaluation and career development for academic staffs in Universiti Teknologi Mara (UiTM) Shah Alam who can be promoted if fulfill the term of promotion. The objectives of this project are 1) to computerize the manual procedure of promotion to web based group decision support system; 2) to construct rules based on the criteria of the staff performance to support the process of evaluation and 3) to determine the staff that qualified to promotion with automatic analysis for purpose candidate recommendation. This project is implementing using Web based asynchronous group decision support system (GDSS) with rule-based system and multi criteria decision making (MCDM) model in developing Electronic Performance Evaluation and Career Development Supporting System. A Web based GDSS provide decision tools and decision support information to its users. All individual evaluator will be automatically aggregated as the group judgement that evaluate the annual performance, competence level (PTK), and 7 general principles at different locations. When all decision issues are resolved, the evaluation by decision makers will be automatically synthesized to provide the final ranking for all candidates under consideration. The rules had been constructing based on criteria of the staff promotion to support the process of evaluation based on hierarchy model of multi criteria decision making technique. The result indicates that the use of the system may help to guide evaluators and able to minimize confusing in choosing the qualified staff for promotion. Thus, this system will reduces the geographical barriers, operating cost and operating time. Consequently, this system also may help improved delivery process of staff information. It is recommended to upgrade the current system to be centralized database through Internet and provide help decision making so that the project will become wider and more useful.